Digital Anticipation: Facilitating the Pre-Emptive Futures of Chinese Grandparent Migrants in Australia. (December 2022) - Baldassar, Loretta; Stevens, Catriona; Wilding, Raelene
In this article, we contrast the digital kinning and digital homing practices of PRC Chinese transnational grandparents in Australia from two migration cohorts. Our case studies demonstrate that these digital practices form an integral part of the ability to anticipate aging futures. This "digital anticipation" not only helps to safeguard and affirm social and cultural identities that are often at risk as people age in migrant settings, but also provides the potential to imagine either a future return to China that involves physical separation from children and grandchildren, or, conversely, a future lived in Australia while still maintaining connection and participating digitally in affective economies that extend beyond the nuclear family to encompass siblings, friends, and lifelong workmates. Here the role of facilitated digital access is highlighted as a form of care that can be provided by younger generations.